Synthesis of bis(indolyl)methanes using ammonium niobium oxalate (ANO) as an efficient and recyclable catalyst - Thurow S. (2015)
© The Royal Society of Chemistry.A green and efficient procedure was developed for the synthesis of bis(indolyl)methanes using ammonium niobium oxalate (ANO) NH4[NbO(C2O4)2(H2O)x]·nH2O as the catalyst and water or glycerol as the solvent. Products were obtained in good to excellent yields under conventional heating (water, 50 °C) or under sonication (glycerol, 110 °C). In the reaction in water, the catalyst was easily reused for further reactions without loss of activity.